Key nutritional factors and interactions during larval development of pikeperch (Sander lucioperca) - El Kertaoui, Najlae; Lund, Ivar; Assogba, Hospice; Dominguez, David; Izquierdo, Marisol; Baekelandt, Sebastien; Cornet, Valerie; Mandiki, Syaghalirwa N. M.; Montero, Daniel; Kestemont, Patrick (Scientific Reports, 2019)
The effects of 8 nutritional variables (Ca/P, Eicosapentaenoic acid (20: 5n-3) + Docosahexaenoic acid (22: 6n-3) (EPA + DHA), Arachidonic acid (20: 4n-6) (ARA), Se, vitamins E, C, D and A) were investigated to identify their respective importance and interactions in pikeperch larval development. In this respect, two modalities (low and high levels) of each variable were tested through a fractional factorial experimental design allowing a reduction from 256 (2(8)) to 16 (2(8-4)) experimental units. Survival was significantly higher in larvae fed a high Ca/P diet while larval growth was significantly lower in larvae fed the same diet variant, associated with a higher incidence of kyphosis and pectoral anomalies in these larvae. Lordosis and scoliosis seemed to be mostly affected by dietary long chain polyunsaturated fatty acids (LC-PUFAs). A significant interaction was shown between n-3 LC-PUFA and vitamin C on jaw anomalies, while myocyte-specific enhancer factor 2C (mef2c) gene expression correlated positively with dietary vitamin C increment. Results also demonstrated an effect of the different nutrients and their interactions on the activity levels of digestive enzymatic activities. The results of the present study highlight the importance of the interactions between Ca/P, LC-PUFAs and vitamins C and E, suggesting their essential roles as key nutritional factors influencing pikeperch larval development. 1,341 3,998 Q1 Q1 SCIE